Participação do sistema nervoso parassimpático no metabolismo energético e na proliferação celular em ilhotas pancreáticas de ratos obesos-MSG - Lubaczeuski, Camila (2013)
The growing number of overweight and obesity has led to an increase in the number of patients with insulin resistance and diabetes mellitus type 2. MSG obese rats were glucose intolerant, insulin resistant and theirs pancreatic islets secrete more insulin in response to glucose. Subdiafragmatic vagotomy changes the response of islets to glucose and improves glucose homeostasis, supporting the hypothesis that an unbalance of autonomic nervous system with increased parasympathetic nervous system (PNS) action but a decreased sympathetic nervous system function. Studies showed that the PNS is also involved in β-cell proliferation. Therefore, we investigated of PNS participation, using a subdiafragmatic vagal denervation, upon pancreatic β-cell function and mass regulation, and the body glucose control disruption in MSG-obese rats. For this, Male Wistar rats received during the first five days of life monosodium glutamate (MSG) or saline. Subdiaphragmatic vagotomy was performed at 30 days of life. At 90 days of age, we verified static insulin secretion, pancreas morphometric, ERK expression in islets, glucose homeostasis and lipidis. The MSG treatment caused obesity at 90 days of life. MSG rats presented lower body weight and nasoanal length, increased Lee index and fat depots, normoglycemia, hyperinsulinemia, dyslipidemia, glucose intolerance and insulin resistance when compared to CTL. Vagotomy performed at 30-days of age prevented obesity, fat deposition in the liver and ameliorated glucose tolerance and insulin sensitivity in adult MVAG rats in relation to MSG rats. Islets from MSG rats secreted more insulin at stimulatory glucose concentrations than CTL islets. Histological analysis showed that pancreatic islets from MSG rats were lower with a reduction in β-cell area without modification in α-cell content when compared with CTL. Also, MSG group presented an increased number of pancreatic islets per mm2, with higher number of islets, which may contributes to the higher islet and β-cell relative mass in the MSG pancreas. These effects were associated with enhanced proliferation in MSG group. The number of MVAG pancreatic islet were less than MSG. Vagotomoy performed at 30-days of age, reduced islet and β-cell area in the pancreas from 90-days old CVAG rats. Finally, the relative islet and β-cell mass in MVAG and CVAG rats was similar to CTL. Here we verified if ERK was involved in β-cell replication in MSG rats, but presented no alteration. We demonstrate for the first time that adult MSG rats showed enhanced pancreatic β-cell proliferation which contributes to the higher islet insulin secretion in response to glucose. The vagus nerve is the main factor involved in such a process, since vagotomy performed at 30 days of age prevented islet morphological alterations in adult MVAG rats. Possibly this increase PNS activity in MSG endocrine pancreas is responsible to hyperinsulinemia that enhanced fat storage, damaged glucose homeostasis and insulin action in MSG obesity